SYNERGISTIC INFLUENCE OF MACRO NUTRIENT, MICRO NUTRIENT AND BIO-FERTILIZER ON ROOT NODULATION, GROWTH AND YIELD OF GARDEN PEA (PISUM SATIVUM L.) - RAJIB DAS; REVA MANDAL; S. B. CHATTOPADHAYAY; UMESH THAPA (The Bioscan, 2015)
An investigation was carried out at Horticultural Research Station, Mondouri, Bidhan Chandra Krishi Viswavidyalaya, Nadia during the autumn-winter season of 2012-13 and 2013-14, to study the synergistic effects of Rhizobium inoculation (bio-fertilizer) along with phosphorus (macro nutrient) and molybdenum (micro nutrient) fertilizers on root nodulation as well as on growth and yield of garden pea. The highest root length of 17.19 cm and number of nodules were counted as 23.68 nodules per plant, when the plants were applied with Rhizobium inoculation along with P @ 40 kg ha-1 and Mo @ 0.5 kg ha-1. Whereas, the highest plant height (79.40cm), number of leaves per plant (22.11) and the heaviest nodules of 386.08 mg was found from 0.5 kg Mo, 80 kg P ha-1 & Rhizobium inoculation. The significantly higher number of pods per plant (108.16), pod weight (9.34 g) and yield ha-1 (13.90 ton ha-1) were found when the plants were provided with Rhizobium inoculation along with P @ 40 kg ha-1 and Mo @ 0.5 kg ha-1